Cellular environment of TTR deposits in an animal model of ATTR—Cardiomyopathy - Teixeira, Cristina; Martins, Helena Sofia; Saraiva, Maria João (Frontiers in Molecular Biosciences, 2023)
Introduction: Cardiac amyloidoses are the most fatal manifestation of systemic amyloidoses. It is believed the number of cases to be greatly underestimated mostly due to misdiagnosis. Particularly, the involvement of TTR V30M in the heart of ATTRV30M amyloidosis has not been completely understood specifically in terms of implicated cellular pathways, heart function and cardiac physiology. In the present work we proposed to characterize TTR V30M cardiac involvement particularly at the tissue cellular level in a mouse model. Methods: HSF ± hTTR V30M mice, a model that expresses human TTRV30M in a Ttr null background, widely used for the characterization and modulation of neurological features of ATTRV30M amyloidosis was used. SDS-PAGE of cardiac homogenates followed by Western blot was performed. Immunohistochemistry and double immunofluorescence analyses were carried out to determine TTR deposition pattern and sub-localization. Results: Western blots were able to detect TTR in its monomeric state at ∼14 kDa. Immunofluorescent images showed TTR was found mostly in the intercellular spaces. Blood contamination was excluded by CD31 staining. Tissues were Congo Red negative. Upon TTR and macrophages (CD68) staining in the cardiac tissue a clear tendency of macrophage convergence to the tissue regions where TTR was more abundant was observed. Moreover, in some instances it was possible to detect co-localization of both fluorophores. Cardiac fibroblasts were stained with PDGFr-alpha, and here the co-localization was not so evident although there was some degree of co-occurrence. The hearts of transgenic mice revealed higher content of Galectin-3. Conclusion: This animal model and associated features observed as result of cardiac TTR deposition provide a promising and invaluable research tool for a better understanding of the implicated pathways that lead to the lethality associated to TTR cardiac amyloidosis. New therapeutic strategies can be tested and ultimately this will lead to improved treatment alternatives capable of increasing patient’s quality of life and life expectancy and, hopefully to eradicate a condition that is silently spreading worldwide.